The World's Desire - Haggard, H. Rider (Henry Rider), 1856-1925; Lang, Andrew, 1844-1912 (Salt Lake City, UT : Project Gutenberg, 2006)
"The World's Desire" by H. Rider Haggard and Andrew Lang is a fantasy novel published in 1890. Odysseus returns to Ithaca after a second journey, only to find his home destroyed by plague and his wife Penelope dead. Guided by a vision of Helen of Troy, he embarks on a final quest to Egypt, where he encounters a treacherous queen, ancient prophecies, and dangerous magic. The novel weaves Greek mythology with the Biblical Exodus in an epic tale of love, loss, and destiny. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_World%27s_Desire
Release date is 2006-04-04
John Bickers, Dagny, Emma Dudding and David Widger
Keywords: Fantasy fiction; Adventure stories; Greece -- Fiction; Odysseus, King of Ithaca (Mythological character) -- Fiction; Helen, of Troy, Queen of Sparta -- Fiction